Предмет: Алгебра,
автор: saska8
Помогите упростить выражение.
Приложения:
Ответы
Автор ответа:
0
получилось так. ответ: -1.
Приложения:
Автор ответа:
0
большое тебе спасибо☺
Автор ответа:
0
не за что).
Автор ответа:
0
a/(2a-b)+(3a-b)/(b-2a)=-a/(b-2a)+(3a-b)/(b-2a)=(-a+3a-b)/(2b-a)=
=(2a-b)(b-2a)=-1
=(2a-b)(b-2a)=-1
Приложения:
Похожие вопросы
Предмет: Математика,
автор: domanetuhleba86
Предмет: Музыка,
автор: gubartanya8
Предмет: Українська мова,
автор: kolesanovaeva
Предмет: Математика,
автор: elena141600
Предмет: Математика,
автор: vikusy2